Synergy of carbon and nitrogen removal of a co-culture of two aerobic denitrifying bacterial strains, Acinetobacter sp. GA and Pseudomonas sp. GP. Issue 38 (13th June 2018) - Guo, Yan; Yang, Ruili; Zhang, Zhaoji; Wang, Xiaojun; Ye, Xin; Chen, Shaohua
Abstract : Two newly isolated aerobic denitrifying bacterial strains ( Acinetobacter sp. GA and Pseudomonas sp. GP) were co-cultured to investigate the synergy of carbon and nitrogen removal of different functional bacteria. Abstract : Two newly isolated aerobic denitrifying bacterial strains ( Acinetobacter sp. GA and Pseudomonas sp. GP) were co-cultured to investigate the synergy of carbon and nitrogen removal of different functional bacteria. The co-culture showed higher efficiency for removing total organic carbon (TOC) and total dissolved nitrogen (TDN) than strain GA or GP cultured separately. The inoculation ratio of 50 (strain GA/GP) was advantageous for the TOC and TDN removal efficiencies of the co-culture. The sequential co-culture tests showed that strain GP being inoculated after strain GA was inoculated for 36 h increased the TDN removal efficiency from 53.3% to 86.8%. This finding indicated that the activity of strain GA was important in the co-culture system, and the sequential co-culture could be advantageous to the synergistic effect of strains GA and GP. The co-culture of different functional bacteria can be an alternative method for improving the performance of aerobic denitrifying microorganisms for pollutant removal.